Wood anatomy of five specie of the Rosaceae family - de la Paz Pérez Olvera, Carmen; Mendoza Aguirre, Mariana; Ceja Romero, Jacqueline; Pacheco, Leticia (Instituto de Ecología, A.C., 2016)
The macroscopic and microscopic anatomical description of the wood of five fruit species of the Rosaceae family is described. Species of Crataegus mexicana Moc & Sessé ex DC. (Hawthorn), Pyrus communis L. (Pear), Pyrus malus L. (Apple) Maloideae subfamily, Prunus armeniaca L. (Peach) and Prunus domestica L. (Plum) Prunoideae subfamily were collected. The state of Puebla, Municipality of San Felipe Teotlalcingo was the collection site. One tree by species was recollected. The macroscopic study was made in wood samples of 15 x 7 x 1 cm and the microscopic study this was made by using slides of dissociated material and cuts from a cube. Samples of wood and slides showed the three typical planes of wood, namely, transverse cross section, tangential and radial. A univariate statistic analysis was performed to the quantitative elements, which were classified according to their average. The five wood species showed similar macroscopic and microscopic characteristics between subfamily, although there were differences between species of the same subfamily, these were stronger between both subfamilies. The purpose of the study was to suggest possible end uses for the wood of fruits trees, since generally speaking this is not used once the trees are no longer productive.